IDENTIFICATION OF SITE CLASS USING MICROTREMOR HVSR MEASUREMENTS IN TANAH KAMPUNG DISTRICT - Gemilang, Rio; Syawalia, Nurlaili; Resta, Ichy Lucya; Adhitya, Bagus; Efendi, Agustian; Sitompul, Jeremia; Rizky Marpaung, Ahmad; Setiawan, Rendy Agus (Prodi Fisika FST UNJA, 2024)
This research was conducted to determine the site class of the soil in the Tanah Kampung District in Sungai Penuh City. In this case, the method used is the HVSR microtremor method. HVSR is a method of comparing the spectrum of the horizontal component to the vertical component of a microtremor wave that recorded by seismograph. HVSR parameters were used to calculated shear wave velocity (Vs30) to defined site class. It reveals this areas classified in site class SC and SD. The area is predominantly composed of SD. This areas are characterized by soft sediments that require special handling if heavy infrastructure development is planned above them. This can be done by compacting the soil layers and mixing them with limestone.